The Rise and Fall of the World's Largest Wine Exporter—And Its Institutional Legacy*. (16th April 2014) - Meloni, Giulia; Swinnen, Johan
Abstract This paper analyzes the causes of the rise and the fall of the Algerian wine industry. It is hard to imagine in the twenty-first century global wine economy, but until about 50 years ago Algeria was the largest exporter of wine in the world—and by a wide margin. Between 1880 and 1930 Algerian wine production grew dramatically. Equally spectacular was the decline of Algerian wine production: today, Algeria produces and exports little wine. There was an important bidirectional impact between developments in the Algerian wine sector and French regulations. French regulations had a major impact on the Algerian wine industry, and the growth of the Algerian wine industry triggered the introduction of important wine regulations in France at the beginning of the twentieth century and during the 1930s. Important elements of these regulations are still present in European wine policy today. (JEL Classifications: K23, L51, N44, N54, Q13)